BERAT LAHIR BAYI TERGANTUNG STATUS GIZI IBU HAMIL - I Made Yase Sanjaya; Retno Sumiyarini (MEDIA ILMU KESEHATAN, 2013)
Background : Intrauterine fetal growth is influenced by maternal nutritional status during pregnancy. Nutritional needs during pregnancy will increase by 25% compared to the normal needs of women. Increase of nutrition needed is required for the growth of the womb, breast, blood volume, placenta, amniotic fluid and fetal growth. LBW is one of the mirrors a country's national health and is a serious problem, because it affects the high rates of infant morbidity and mortality as well as the quality of future generations. Therefore, we do the studies about the effect of nutritional status of pregnant women to the incidence of LBW. Objective : Knowledgeable influence the nutritional status of mothers during pregnancy on the incidence of LBW Methods : The study design used in this study is a survey of analytical, case-control study design. The number of samples used were 54 respondents from RSUD Wates. Analysis of the data used is the analysis of univariate and bivariate analysis using Chi-square and look for the Odds Ratio (OR) with a significance level of 0.05. Result: Mothers who give birth babies with low birth weight is dominated by the mother during pregnancy suffer from chronic energy deficiency (55.56%), whereas mothers who gave birth babies with suffient birth weight tend not to suffer from chronic energy deficiency during pregnancy or NON CED (74%). There is a significant relationship and influence between the nutritional status of pregnant women with the incidence of LBW in RSUD Wates (p-value = 0.027, OR = 3.571, CI = 95%). Conclusion: Nutritional status of mothers during pregnancy has a significant relationship with the incidence of low birth weight, and mothers who suffer from chronic energy deficiency during pregnancy has 3.571 times greater risk for low birth weight babies compared with mothers who NON CED. Keywords : Nutritional status of pregnant women, CED, low birth weight